Identification of serotype 1-, 3-, and 6-specific antigens of Ureaplasma urealyticum by using monoclonal antibodies. - Cheng, X (1994)
Little is known about the antigens responsible for serotype specificity in Ureaplasma urealyticum. We produced monoclonal antibodies to U. urealyticum serotypes 1, 3, and 6, the serotypes most commonly found in pregnant women, and analyzed serotype-specific antigens for the three serotypes. Clinical isolates belonging to serotype 1, 3, or 6 were tested in immunoblots with these monoclonal antibodies. The immunoblot patterns of these isolates were, in most cases, different from each other as well as from those of the reference strains, indicating a high rate of antigenic variation among U. urealyticum strains.